GENETIC DIVERSITY BASED ON GROWTH VARIABLES OF THREE BAMBARA GROUNDNUT LANDRACES (Vigna subterranea (L.) VERDCOURT) - Endah Sri Rejeki; Suhaili Suhaili; Rahmad Jumadi; R. Agustina; W. Lailiyah; setyo budi (TROPICROPS (Indonesian Journal of Tropical Crops), 2020)
Bambara groundnut has competitive nutritional value such as 49–63.5% carbohydrate, 15–25% protein, and 4.5–7.4% fat. There is not available yet a superior variety. Bambara Groundnut Research Centre has been working intensively to select the candidates of superior variety. Three of bambara groundnut pure lines of BGRC seed collection, including Gresik (Gresik), GHC (Gresik) and S19-3 (Namibia) assessed based on their growth traits, including germination rate, number of leaves, plant height (cm), length of petiole (cm), length of internode (cm), growth type, 1st flowering (das) and 50% of flowering (das) in the Gresik field 5 m above sea level, with Random Complete Block Design experiment, three replicates. Analysis of means (ANOM) calculated to test differences between landraces in particular traits. Heritability of three pure lines calculated based on Mean Square Estimated of Analysis of Variance (ANOVA), as well as coefficient correlation, using Minitab 18. The result showed that S19-3 as an introduced landrace from Namibia has traits similarity to the two landraces, namely GHC and Gresik except days to 50% flowering time. Analysis of means shows that S19-3 has days to 50% flowering early compare to the others. The trait of 50% flowering time (dap) also shows a high heritability (0.58). First flowering time has a significant correlation with 50% flowering time in positive direction.